Associations of ambient fine particulate matter and its constituents with serum complement C3 in a panel study of older adults in China. (September 2019) - Pei, Lu; Zhao, Meiduo; Xu, Jing; Li, Ang; Luo, Kai; Li, Runkui; Yang, Mingan; Xu, Qun
Abstract: Epidemiological studies have demonstrated association between the total mass of fine particulate matter (PM2.5 ) exposures and inflammation. There are few studies exploring the associations between PM2.5 constituents and the biomarkers of inflammation in older adults and the underlying biological mechanisms are not exact. In this study, we examined the associations between PM2.5 and its constituents (organic carbon (OC), elemental carbon (EC), total carbon (TC), polycyclic aromatic hydrocarbons (PAHs) and complement three factor (C3), an important biomarker of inflammation in a repeated panel of 175 older adults in Beijing, China. We have constructed three different linear mixed effect models (single-pollutant model, constituent-PM2.5 joint model, and constituent-residual model) to evaluate the association of PM2.5 and its constituents and complement C3, controlling for concentration of high sensitive C-reactive protein (hs-CRP), day of week, mean temperature, relative humidity, location and potential individual confounders. We found robust positive associations of OC, EC, TC, PAHs and PM2.5 mass concentration with complement C3 at different lag patterns. The cumulative effects of pollutants increased across average of 2–5 days. Individuals aged 65 and above, or with diabetes, or BMI ≥30, or with no-cardiopathy, or with hypertension also exhibited positive associations between PM2.5 and complement C3. The results revealed that short-term exposure to PM2.5 and its constituents could result in a significant increase in serum level of complement C3. These findings suggested a possible involvement of complement C3 in the effect of PM2.5 on inflammatory reaction. Graphical abstract: Image 1 Highlights: Highlights. Short-term exposure to PM2.5 and its constituents could result in a significant increase in complement C3. The first study examining complement C3's role in the effect of PM2.5 on inflammatory reaction. Complement C3 may mediate the effect of PM2.5 on inflammatory reaction. Abstract : Short-term exposure to PM2.5 and its constituents could result in a significant increase in complement C3, which may mediate the effect of PM2.5 on inflammatory reaction.